There is Something about Marrying… The Case of Human Rights vs. Migration Regimes using the Example of Austria - Irene Messinger (Laws, 2013)
States pursue various juridical strategies to prevent ‘marriages of convenience’ seen as undermining tightening migration regimes. This article examines how Austrian Alien Law constitutes entering into such a marriage as a criminal offense and looks at the legal proceedings in district courts in Vienna where most cases of alleged ‘marriages of convenience’ are being dealt with. It also studies the work of the Viennese branch of alien police investigating into this offense. These practices are often in conflict with Article 8 and 12 of the European Convention of Human Rights, granting the right to respect for private and family life and the right to marry.